Some Evidences of Sanskrit literature in Indian Classical Dance Tradition - Balakailasanathasarma, M. (Eastern University, Sri Lanka, 2022)
Dance as a way of life is as old as humanity itself. It evolved as one of the activities of mar. It is not surprising to assume that facial expressions, hand gestures and movements of various limbs were used as a means of expressions, one's own emotions even before the formation of language. These symbols along with sounds were converted into a form of language. The speech is a great opening for the systematized activities of man in all walks of life. At this stage through singing and dancing men collectively expressed their happiness. Of course, the songs and dance movements were spontaneous without any specific organisation. The growth and development in the field of religion, literature lan- guage and tradition led to the formation of systematic and stylised forms in the various branches of fine arts in Indian Classical Dance.Indian Dance has a specific and sentimen- tal background. Dance styles as practised today in different regions of India are different from one another in their exposition although they have a common origin. Pre-historic dance was primitive. The Fine Arts of Indian Classical Dance forms are mainly the con- tribution of hindu religion and religious literature in Sanskrit. The Fine Arts of dance, music, drama, sculpture, painting and folk dance have common objective although they follow different means and techniques in their exposition. The subject of theory they deal it is supported by hindu thought, philosophy and mythology. The Sanskrit literature pre- scribed particular spirits to denote specific directions and purposes.
Keywords: Classical Dance; Fine Arts; Sanskrit literature; Tradition